Conflict and Peace Reportage in Nigeria Newspaper: A Reappraisal of Punch and Daily Trust Newspaper (January – July, 2019) - Paul Timileyin Aleyomi (Syntax Corporation Indonesia, 2023)
Abstract This study investigates the coverage of conflict and peace issues in Nigerian newspapers, specifically focusing on Punch and Daily Trust. The research aims to achieve three primary objectives: assess the frequency of conflict and peace reportage in both newspapers, determine the level of prominence given to these issues by Punch and Daily Trust, and identify the categories under which such issues are reported. The study draws on the Agenda-Setting Theory and Framing Theory to provide a comprehensive analysis. Using a quantitative content analysis approach, the study examines stories related to conflict and peace issues published in the selected newspapers from January 2019 to July 2019. The key findings reveal distinct patterns in the reportage of conflict and peace matters. Punch exhibits a higher emphasis on certain categories like